2014
DOI: 10.1159/000354047
|View full text |Cite
|
Sign up to set email alerts
|

A Calcium Prerinse Required to Form Calcium Fluoride in Plaque from a Sodium Fluoride Rinse

Abstract: The purpose of this study is to determine whether a calcium (Ca) prerinse used before a 228 µg/g (ppm) fluoride (F) rinse would induce the formation of ‘calcium fluoride-like' (CaF2-like) deposits in human dental plaque. Sixty minutes after the use of the Ca prerinse/F rinse, plaque samples were collected from 10 volunteers, homogenized, and split into 2 aliquots. The plaque mass from one aliquot was then extracted with a ‘plaque-like' solution that extracted all the CaF2-like deposits. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In any case, the very large increase in biofilm F in both these studies, as well as the 12× increase in this parameter found in samples of biofilm collected from human teeth 1 h after use of this same Ca prerinse/250 ppm F rinse combination [Vogel et al, 2008a], appear to explain the high level of protection against demineralization observed here. Such biofilm F trapping is consistent with the fixing of fluoride by a Ca mechanism by which the rinse has been postulated to increase oral levels of fluoride [Rose et al, 1996;Vogel et al, 2008aVogel et al, , 2008bVogel et al, , 2011Vogel et al, , 2014. Although the nature of such biofilm reservoirs requires further investigation, recent studies have suggested that, unlike a conventional F rinse [Vogel et al, 2010], the Ca prerinse has been shown to deposit nearly 30% of its F as calcium fluoride-like precipitates .…”
Section: Discussionsupporting
confidence: 58%
“…In any case, the very large increase in biofilm F in both these studies, as well as the 12× increase in this parameter found in samples of biofilm collected from human teeth 1 h after use of this same Ca prerinse/250 ppm F rinse combination [Vogel et al, 2008a], appear to explain the high level of protection against demineralization observed here. Such biofilm F trapping is consistent with the fixing of fluoride by a Ca mechanism by which the rinse has been postulated to increase oral levels of fluoride [Rose et al, 1996;Vogel et al, 2008aVogel et al, , 2008bVogel et al, , 2011Vogel et al, , 2014. Although the nature of such biofilm reservoirs requires further investigation, recent studies have suggested that, unlike a conventional F rinse [Vogel et al, 2010], the Ca prerinse has been shown to deposit nearly 30% of its F as calcium fluoride-like precipitates .…”
Section: Discussionsupporting
confidence: 58%
“…Such a result suggests that the nonfluoride components of fluoride dentifrices and rinses, in particular surfactants such as SLS, can be manipulated to improve the fluoride release characteristics from oral fluoride reservoirs following conventional topical fluoride treatments. The characterization of the effect of these components on these reservoirs, perhaps using a recently described extraction technique [Vogel et al, 2010[Vogel et al, , 2014, combined with recent procedures shown to greatly increase the amount of these reservoirs [Vogel et al, 2006a[Vogel et al, , b, 2008a, may lead to the development of topical agents that induce a much larger and more sustained increase in oral fluid fluoride. Treatments based on this approach could potentially have a much larger cariostatic effect than can be obtained with current fluoride topical agents with the same fluoride dose.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the concept that fluoride bound to the bacteria in dental biofilms is a function of the surrounding (fluid) fluoride concentration [Vogel et al, 2010[Vogel et al, , 2011, i.e., with a decrease in availability in the fluid, there is also a release of the fluoride that was bound to the bacteria via calcium bridges. In addition, this gives support to the importance of other fluoride sources in dental biofilm, such as calcium fluoride [Vogel et al, 2011[Vogel et al, , 2014, in order to achieve persistent fluoride release patterns and increased anticaries potential [Souza et al, 2016].…”
Section: Discussionmentioning
confidence: 76%